Implementation of Public Complaint Services in Badung Regency Based on E-Government - Pradnyawati, Ni Wayan Intan; Widhi Antari, Ni Putu Bayu (Universitas 17 Agustus 1945 Surabaya, 2024)
In this research, researchers discuss the implementation of the SIDUMAS application in serving complaints from the Badung Regency community. Using a qualitative descriptive approach, this research discusses implementation using Ripley and Franklin's success factors and implementation success criteria. The results of this research show that the implementation of the SIDUMAS application is good in terms of bureaucratic compliance. However, it is still not optimal in terms of smooth routine and there are still several problems. The implementation and targeted impacts are still less than optimal. Judging from the account registration process, people have to wait for the data verification process for approximately one week. Some people also think that the registration process is complicated and needs to be simplified. Currently the SIDUMAS application is not yet able to reach smartphones based on Android and iOS with the latest version. Likewise, if we look at the targeted benefits of the SIDUMAS application, it cannot be said to be optimal because it cannot be used by the people of Badung Regency as a whole.